2018
DOI: 10.1073/pnas.1800562115
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of gasdermin D recognition by inflammatory caspases and their inhibition by a gasdermin D-derived peptide inhibitor

Abstract: The inflammasomes are signaling platforms that promote the activation of inflammatory caspases such as caspases-1, -4, -5, and -11. Recent studies identified gasdermin D (GSDMD) as an effector for pyroptosis downstream of the inflammasome signaling pathways. Cleavage of GSDMD by inflammatory caspases allows its N-terminal domain to associate with membrane lipids and form pores that induce pyroptotic cell death. Despite the important role of GSDMD in pyroptosis, the molecular mechanisms of GSDMD recognition and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 134 publications
(92 citation statements)
references
References 38 publications
(40 reference statements)
2
89
1
Order By: Relevance
“…Recent discoveries surrounding the mechanisms which regulate the expression and activation of IL‐1 family members are also opening possibilities for novel approaches to target these pathways e.g. through NLRP3, protease and gasdermin D/pyroptosis inhibitors . While a greater understanding of the specific, and often unique, roles each family member plays in driving systemic and tissue specific inflammatory responses will expedite these endeavours, some significant gaps in our knowledge still remain.…”
Section: Resultsmentioning
confidence: 99%
“…Recent discoveries surrounding the mechanisms which regulate the expression and activation of IL‐1 family members are also opening possibilities for novel approaches to target these pathways e.g. through NLRP3, protease and gasdermin D/pyroptosis inhibitors . While a greater understanding of the specific, and often unique, roles each family member plays in driving systemic and tissue specific inflammatory responses will expedite these endeavours, some significant gaps in our knowledge still remain.…”
Section: Resultsmentioning
confidence: 99%
“…The catalytic domain of caspases will directly bind to GSDMD and its cleavage site peptide fltd [80]. Ac-FLTDcmk, a GSDMD-derived peptide inhibitor, can inhibit the cleavage of GSDMD by binding directly to the core catalytic domain of caspase-1, caspase-4, caspase-5, and caspase-11.…”
Section: Therapeutic Prospects Of Targeting Inflammasomes In Renal DImentioning
confidence: 99%
“…GSDMD KO macrophages treated with LPS and nigericin showed that IL-1β release was dependent on GSDMD and that these cells are resistant to pyroptosis. To validate the specificity for GSDMD in mediating IL-1β release, a peptide inhibitor, N-acetyl-Phe-Leu-Thr-Asp-chloromethylketone (Ac-FLTD-CMK) 29 To determine if the caspases specifically interacted with each other, COS-7 cells were transfected with pro-caspase-1, procaspase-4, and pro-IL-1β plasmids. We used COS-7 cells as they are easy to transfect with more than 90% transfection efficiency using GFP and they do not express ASC or NLRP3, facilitating the interactions between the caspases independent of the inflammasome complex (Fig.…”
Section: E Histolytica-induced Gsdmd Cleavage Regulates Il-1β Secretionmentioning
confidence: 99%